Information Technology Self-Efficacy and Library Portal Use in Nigerian Universities - Ajisebutu, Adenike Elizabeth; Adetayo, Adebowale; Okediji, Oyekanmi Gabriel; Enamudu, Augustine I. (Journal of Digital Learning and Education, 2024)
This descriptive cross-sectional survey aimed to investigate the relationship between information technology self-efficacy and the use of library portal services among undergraduate students in selected universities in South-West Nigeria. A cross-sectional survey used stratified sampling to select 658 undergraduates from three Nigerian universities: University of Ibadan, University of Lagos, and Babcock University. The results revealed a high level of IT self-efficacy among respondents (mean=3.48) and significant use of library portals, particularly for research needs like finding scholarly materials (mean=3.50), accessing indexing services (mean=3.43), and seeking reference assistance (mean=3.39). Library computers were the most preferred access point (mean=3.11). A strong, significant positive correlation was found between IT self-efficacy and library portal use (r=0.609, p<0.05), indicating that greater self-efficacy in using IT corresponded with higher utilization of library portals and their services. The findings highlight the importance of fostering IT skills and self-confidence among students to facilitate effective use of digital library resources.